Keeping their distance? Odor response patterns along the concentration range - Strauch, Martin; Ditzen, Mathias; Galizia, Cosmas G. (Frontiers in Systems Neuroscience, 2012)
We investigate the interplay of odor identity and concentration coding in the antennal lobe of the honeybee Apis mellifera. In this primary olfactory center of the honeybee brain, odors are encoded by the spatio-temporal response patterns of olfactory glomeruli. With rising odor concentration, further glomerular responses are recruited into the patterns, which affects distances between the patterns. Based on calcium-imaging recordings, we found that such pattern broadening renders distances between glomerular response patterns closer to chemical distances between the corresponding odor molecules. Our results offer an explanation for the honeybee's improved odor discrimination performance at higher odor concentrations.